2022
DOI: 10.1146/annurev-environ-120420-085027
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cooling in a Warming World: Technologies, Cultures, and Circularity

Abstract: Cooling is fundamental to quality of life in a warming world, but its growth trajectory is leading to a substantial increase in energy use and greenhouse gas emissions. The world is currently locked into vapor-compression air conditioning as the aspirational means of staying cool, yet billions of people cannot access or afford this technology. Non–vapor compression technologies exist but have low Technological Readiness Levels. Important alternatives are passive cooling measures that reduce mechanical cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 141 publications
0
7
0
Order By: Relevance
“…These results agree with Kim et al [35] who reported that open windows combined with green roofs provided better thermal comfort and reduced the need for mechanical cooling systems. In contrast, Radhika et al [36] showed that the combination of cool roofs and open windows enhanced indoor thermal comfort by reducing heat gain. However, the results of this study suggest that the combined use of green and cool roofs can provide a promising solution for reducing urban heat island effects and improving building energy efficiency The results of the open window condition for all four types of roofs showed that the temperatures were generally lower compared to the closed window condition.…”
Section: Comparative Analysis Of Combined Roof Effects On Temperature...mentioning
confidence: 94%
“…These results agree with Kim et al [35] who reported that open windows combined with green roofs provided better thermal comfort and reduced the need for mechanical cooling systems. In contrast, Radhika et al [36] showed that the combination of cool roofs and open windows enhanced indoor thermal comfort by reducing heat gain. However, the results of this study suggest that the combined use of green and cool roofs can provide a promising solution for reducing urban heat island effects and improving building energy efficiency The results of the open window condition for all four types of roofs showed that the temperatures were generally lower compared to the closed window condition.…”
Section: Comparative Analysis Of Combined Roof Effects On Temperature...mentioning
confidence: 94%
“…Behavioral adaption is one effective strategy to cool down the body temperature, and such a strategy is often related to enhanced heat dissipation through thermal conduction and thermal convection. 29 For example, ducks like to jump into the river in the hot summer, which can transfer the excessive heat to the cool water. Butterflies and many other birds spread their wings to accelerate convection heat dissipation.…”
Section: Thermal Energy Regulation In Biological Systemsmentioning
confidence: 99%
“…For organisms living in hot habitats, efficient heat dissipation can protect organisms from overheating. Behavioral adaption is one effective strategy to cool down the body temperature, and such a strategy is often related to enhanced heat dissipation through thermal conduction and thermal convection . For example, ducks like to jump into the river in the hot summer, which can transfer the excessive heat to the cool water.…”
Section: Thermal Energy Regulation In Biological Systemsmentioning
confidence: 99%
“…In locations with infrastructure and resources, cooling technologies such as air conditioners, fans, and cooling centers are used to cope with extreme heat. However, these technologies are not currently sustainable, and a great deal more effort will be needed to make cooling technologies more efficient and/or to increase knowledge of how to behaviorally cope with heat (Khosla et al 2022).…”
Section: Hot Climate Acclimatizationmentioning
confidence: 99%